Metabolomic Profiling Reveals Changes in Amino Acid and Energy Metabolism Pathways in Liver, Intestine and Brain of Zebrafish Exposed to Different Thermal Conditions - Aguilar, Andrea; Mattos, Humberto; Carnicero, Beatriz; Sanhueza, Nataly; Muñoz, David; Teles, Mariana; Tort, Lluis; Boltaña, Sebastian (Frontiers in Marine Science, 2022)
Global warming is predicted to increase prolonged thermal challenges for aquatic ectotherms, i.e. it can cause metabolic performance declines, impact food intake, and finally cause an impaired growth. In this research work, we asked whether a tropical fish Danio rerio (zebrafish) were able to tolerate prolonged thermal challenges and if the temperature increase caused a significant impact in the growth and metabolism. To answer our questions, we evaluated the metabolomic performance, a question that has received little attention so far, using differential chemical isotope labelling (CIL) liquid chromatography-mass spectrometry (LC-MS) . Three groups of fish were exposed to various temperatures 27.6 ± 2 °C, 30.7 ± 2° C or 32.2 ± 2º C during 270 days post fecundation (dpf) to evaluate the impact of the temperature increase on the growth and metabolomic performance. The obtained results demonstrated different metabolomic changes in response to acclimation to the different temperatures. After 270 days, the fish kept at the highest tested temperature (32 °C) showed reduced growth, reduced condition factor, and elevated levels of metabolites associated with amino acid catabolism and lipid metabolism pathways in the liver and intestine, compared with fish kept at lower temperatures (27.6 ± 2 °C). These findings demonstrated a clear redistribution of energy stores and protein catabolism in fish at the highest temperature thus showing a preference for maintaining length growth during times of limited energy availability. Moreover, herein we also screened out both the marker metabolites and the altered metabolic pathways, with the aim of providing important insights to ascertain the effects of the water temperature increase on the growth and development of tropical fish.